Schinopsis brasiliensis Engler-Phytochemical Properties, Biological Activities, and Ethnomedicinal Use: A Scoping Review - Ladaha Pequeno Menna Barreto Linhares; Bruna Vanessa Nunes Pereira; Maria Karoline Gomes Dantas; Wislayne Mirelly da Silva Bezerra; Daniela de Araújo Viana-Marques; Luiza Rayanna Amorim de Lima; Pedro Henrique Sette- (MDPI AG, 2022)
Brazil has the most incredible biodiversity globally and has a vast storehouse of molecules to be discovered. However, there are no pharmacological and phytochemical studies on most native plants. Parts of Schinopsis brasiliensis Engler, a tree from the Anacardiaceae family, are used by several traditional communities to treat injuries and health problems. The objective of this scoping review was to summarize the pharmacological information about S. brasiliensis, from ethnobotanical to phytochemical and biological studies. Data collection concerning the geographical distribution of S. brasiliensis specimens was achieved through the Reflora Virtual Herbarium. The study's protocol was drafted using the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). The search strategy used the keyword "Schinopsis brasiliensis" in the databases: PUBMED, EMBASE, SCOPUS, Science Direct, Web of Science, SciFinder, and SciELO. Rayyan was used for the selection of eligible studies. In total, 35 studies were included in the paper. The most recurrent therapeutic indications were for general pain, flu and inflammation. The bark was the most studied part of the plant. The most used preparation method was decoction and infusion, followed by syrup. Phytochemical investigations indicate the presence of tannins, flavonoids, phenols, and polyphenols. Most of the substances were found in the plant's leaf and bark. Important biological activities were reported, such as antimicrobial, antioxidant, and anti-inflammatory. S. brasiliensis is used mainly by communities in the semi-arid region of northeastern Brazil to treat several diseases. Pharmacological and phytochemical studies together provide scientific support for the popular knowledge of the medicinal use of S. brasiliensis. In vitro and in vivo analyses reported antimicrobial, antioxidant, anti-inflammatory, antinociceptive, cytotoxic, photoprotective, preservative, molluscicidal, larvicidal, and pupicidal effects. It is essential to highlight the need for future studies that elucidate the mechanisms of action of these phytocompounds.